EVALUASI PENGANGGARAN, PENGALOKASIAN, DAN PELAPORAN DANA DESA BERAKIT - Salihi, Salihi; Annisa Rahmah Niami; Alya Ningsih Bailey; Fazira Aulia; Melia Yolanda; Priti Ramdini Syafitri; Ragitha Septhi Pratiwi; Sri Rahayu Delsya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Berakit Village is located in the administrative area of ​​Bintan Regency, Teluk Sebong District. Village funds start from planning programs and activities, community implementation. Group 6 KKN carried out socialization in the form of targets and input for land development carried out by the Village Head and then given to BUMDes Berakit, which has the aim of improving the economy of the assembled community by managing land and maximizing the use of the budget so that it is on target. In this socialization it went well and also received a pretty good response, the result of this program of activities was that the Berakit Village community was enthusiastic regarding the development and management of land, budgeting, allocation and reporting of the use of village fund budgets which they hoped would advance tourism, SMEs, and improve the economy of Berakit Village. In addition, they hope that the existing village fund budget can be allocated properly and its use is prioritized on things that have the potential so that it will generate a large benefit in the future